University Students’ Hangover May Affect Cognitive Research - Murgia, Mauro; Mingolo, Serena; Prpic, Valter; Sors, Fabrizio; Santoro, Ilaria; Bilotta, Eleonora; Agostini, Tiziano (Frontiers in Psychology, 2020)
University students are the most employed category of participants in cognitive research. However, researchers cannot fully control what their participants do the night before the experiments (e.g., consumption of alcohol) and, unless the experiment specifically concerns the effects of alcohol consumption, they often do not ask about it. Despite previous studies demonstrating that alcohol consumption leads to decrements in next-day cognitive abilities, the potential confounding effect of hangover on the validity of cognitive research has never been addressed. To address this issue, in the present study a test-retest design was used, with two groups of university students: at T0, one group was constituted by hungover participants, while the other group was constituted by non-hungover participants; at T1, both groups were re-tested in a non-hangover state. In particular, the tests used were two versions of a parity judgement task, and an arithmetic verification task. The results highlight that: a) the response times of university students experiencing a hangover are significantly slower than those of non-hangover students; b) the response times of hungover students are slower than those of the same students when re-tested in a non-hangover state. Additionally, it was also observed that the prevalence of hungover students in the university campus varies depending on the day of the week, with a greater chance of enrolling hungover participants on specific days. In light of the latter result, the recruitment of university students as participants in cognitive experiments might lead researchers to erroneously attribute their results to the variables they are manipulating, ignoring the effects of the potential hangover state.